Strategy For Ecotourism Development In Efforts To Improve Community Welfare In Ayung River Flow (Case Study of Tukad Bindu, Kesiman Village, Denpasar City) - Luh Putu Kirana Pratiwi; Ni Made Kencana Maharani (SEAS (Sustainable Environment Agricultural Science), 2021)
Management of ecotourism-based tourism areas can create sustainable tourism. River revitalization in Denpasar City is one of the Denpasar City government work programs that aims to provide environmental education, environmental preservation and have economic potential in empowering the community's economy. The existence of rivers in Bali is still preserved to realize the implementation of Tri Hita Karana, which is maintaining good relations with God, nature, and humans so that the presence of water in Bali must be maintained in terms of quality and quantity. This study aims to explore the potential and development strategies of ecotourism to prosper the Ayung River flow in the city of Denpasar. Alternative strategies that need to be done to improve the welfare of the community are through intensive urban agriculture development, increasing agricultural productivity, tourism attractions, preserving the environment of the river, improving the quality of managers by empowering all stakeholders, and improving the community's economy with tourism activities that are carried out continuously. The government through related agencies is expected to facilitate consistently marketing access to agricultural products, tourism promotion through various major events of the Office to be held in Tukad Bindu so that economic improvement can be achieved significantly